2021
DOI: 10.23887/jp2.v4i2.35044
|View full text |Cite
|
Sign up to set email alerts
|

POP-UP Book Daur Hidup Hewan

Abstract: Kurangnya kreatifitas guru dalam mengembangkan media pembelajaran, khususnya pada mata pelajaran IPA yang menyebabkan kegiatan pembelajaran tidak berjalan dengan optimal sehingga menyebabkan beberapa siswa belum mencapai nilai KKM pada nilai kompetensi pengetahuan IPA. Oleh karena itu, perlu adanya pengembangan media pembelajaran yaitu media Pop-Up Book. Penelitian ini bertujuan untuk mendeskripsikan proses pengembangan media pembelajaran Pop-Up Book dan mengetahui validitas hasil pengembangan media pembelajar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 20 publications
0
0
0
Order By: Relevance
“…Referring to the study of research results conducted by (Winarti &;Setiani, 2019) that there are significant differences in the use of pop-up books on student learning outcomes. In line with this research (Putu &;Novita, 2021) concluded that pop-up book media is effective and optimally helps students understand the material and improve learning outcomes.…”
Section: Introductionsupporting
confidence: 58%
“…Referring to the study of research results conducted by (Winarti &;Setiani, 2019) that there are significant differences in the use of pop-up books on student learning outcomes. In line with this research (Putu &;Novita, 2021) concluded that pop-up book media is effective and optimally helps students understand the material and improve learning outcomes.…”
Section: Introductionsupporting
confidence: 58%
“…Pembelajaran yang menarik perhatian peserta didik adalah pembelajaran yang menggunakan media yang menarik dan menyenangkan serta sinkron dengan siswa (Ningtyas, 2019). Media pembelajaran akan membuat materi yang bersifat abstrak menjadi lebih nyata (Novita, 2021). Penggunaan media pembelajaran yang tepat dapat meningkatkan efisiensi pembelajaran.…”
Section: Introduction *unclassified